(untitled) (E Conference Zone, 2022)
The article is devoted to the study of the significance of artistic creativity in national culture, using the example of the work of Tleubergen Zhumamuratov. On the basis of a consistent analysis, the significance of the poet’s heritage in the modern world, in national literature and poetic space is determined. From the point of view of modernity, the article comprehends the ideological and thematic orientation, genre features and artistic skill, the multifaceted heritage of Tileubergen Kupbatulla uly Zhumamuratov. Questions are raised about perpetuating the name of the poet-philosopher.